Age and sex‐specific reference intervals for prooxidant‐antioxidant balance, anti‐heat‐shock protein 27 (anti‐hsp27), and routine laboratory tests in the middle‐aged adult population. (7th August 2021) - Ghazizadeh, Hamideh; Bohn, Mary Kathryn; Yaghooti‐Khorasani, Mahdiyeh; Ghaffarian‐Zirak, Roshanak; Valizadeh, Mohsen; Saberi‐Karimian, Maryam; Safarian, Hamideh; Kamel‐Khodabandeh, Atieh; Zare‐Feyzabadi, Reza; Timar, Ameneh; Mohammadi‐Bajgiran, Maryam; Oladi, Mohammad Reza; et al.
Abstract: Introduction: We aimed to define specific reference intervals (RIs) for 11 biomarkers including inflammatory and oxidative stress biomarkers, liver, and renal function tests in a healthy Iranian adult population for the first time. Methods: CLSI Ep28‐A3 guidelines were then used to calculate accurate age‐ and sex‐ as well as body mass index (BMI)‐specific RIs. Results: RIs for studied biomarkers showed no significant age and sex‐specific differences, except for uric acid, which had higher concentrations in men when compared to women. Additionally, after partitioning the participants based on the BMI with a cutoff point of 25 kg/m 2, only the levels of hs‐CRP were positively associated with higher BMI (RI for BMI>25: 0.51–7.85 mg/L and for BMI<25: 0.40–4.46 mg/L). RI for PAB and anti‐hsp‐27 were reported 4.69–155.36 HK and 0.01–0.70 OD in men and women aged 35–65 years old. Conclusion: Partitioning by sex and BMI was only required for uric acid and hs‐CRP, respectively, while other biomarkers required no partitioning. These results can be expected to valuably contribute to improve laboratory test result interpretation in adults for improved monitoring of various diseases in the Iranian population. Abstract : Biosensor: Telediagnosis & Remote Digital Imaging